Soil Fertility Status and Correlation of Available Macro and Micronutrients in Chambal Region of Madhya Pradesh - and S.K. Dubey, Y.P. Singh, B.P.S. Raghubanshi, Rajbeer S. Tomar, S.K. Verma (Journal of the Indian Society of Soil Science, 2015)
Fertility status of alluvial and medium black soils and ravinous land, and their correlation studies were carried out for Chambal region of Madhya Pradesh. The alluvial and medium black soils were neutral to alkaline, whereas ravinous land was more or less neutral. In general, the soils were low in soluble salts, organic carbon and calcium carbonate content. The ranges of available N, P, K and S were 126 to 361, 7.0 to 29.5, 128 to 391 and 6.8 to 33.5 kg ha-1 in alluvial soil; 178 to 408, 7.9 to 28.8, 122 to 386 and 8.5 to 34.4 kg ha-1 in medium black soil and 125 to 301, 6.2 to 25.3, 252 to 406 and 11.5 to 38.8 kg ha-1 in ravinous land, respectively. Of alluvial soil samples, 97% were low and 3% medium in N; 14% low, 68% medium and 18% high in P; 1% low, 35% medium and 64% high in K and 59% low and 41% medium in S. Of medium black soil samples, 90% were low and 10% medium in N; 21% low, 69% medium and 10% high in P; 4% low, 37% medium and 59% high in K and 51% low and 49% medium in S. Of ravinous land soil samples, 95% were low and 5% medium in N; 68% low and 32% medium in P; 19% medium and 81% high in K and 24% low and 66% medium in S. As regards deficiency of micronutrients, 64.5, 11.7, 14.3 and 14.5% were deficient in Zn, Fe, Mn and B, respectively in alluvial soils; 76.3, 33.3, 8.8, 8.6 and 5.1% were deficient in Zn, Fe, Mn, B and Mo, respectively in medium black soils and 18.4 and 15.8% were deficient in Zn and B, respectively in ravinous land. Available N, P, K, S, Fe, Cu, Zn, Mn and B were negatively and significantly correlated with pH, whereas Mo showed positive correlation. Available N and P were significantly and negatively correlated with EC, but positively correlated with K and S. Available N, P, K, S, Fe, Cu, Zn, Mn, B and Mo were significantly and positively correlated with organic carbon and silt plus clay content in soil, whereas available Zn, Fe, Cu, Mn, B and Mo were significantly and negatively correlated with CaCO3 content in soil.